Mechanical properties of low concentration alkaline activated crimped steel fibre reinforced geopolymer concrete - Murthy, A. Sreenivasa; Patil, M.B.; Naik, C. Maya (Journal of Structural Engineering, 2024)
Cement manufacturing is one of the major causes of carbon dioxide (CO2) emissions. The construction sector focuses on sustainability as a key factor in reducing stress on the environment by implementing innovative materials and techniques. The application of geopolymer concrete (GPC) is one such emerging technology in reducing CO2 emissions by completely replacing cement. In this research, it is intended to prepare alkali-activated GPC having a compressive strength of 30-40 MPa using industrial wastes i.e., Fly Ash (FA) and ground granulated blast furnace slag (GGBS) as binders. Sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) were used as alkaline activators while natural sand (river sand) and Crushed Stone Sand (CSS) were used as fine aggregates and Crimped Steel Fibres (CSF) were used in synthesising the GPC. Results showed that the maximum compressive strength of was observed to be 46 MPa and 45 MPa for river sand and crushed stone sand utilised GPC respectively using 5 molar NaOH and Na2SiO3 solutions under ambient curing conditions. Furthermore, the addition of CSF showed significant improvement in mechanical properties such as tensile strength, shear strength, flexure strength and bond strength of GPC. This synthesized GPC can be effectively applied for various applications such as building construction, precast structural components, road construction etc.